Les savoirs professionnels des conseille.r.e.s principaux/(p)ales d’éducation débutant.e.s construits dans un dispositif de formation en situation de travail, en matière de régulation de l’équipe de vie scolaire - Claude Javier (Éducation et Socialisation)
The professional learning of beginner Principal Education Advisors (CPES) remains a poorly documented issue. This article identifies the professional knowledge constructed by CPES in the regulation of the school life team, during their participation in a work-based training program. The text presents some of the results of a research-intervention conducted as part of the training of CPE mentors responsible for supporting CPES. After setting out the tensions relating to learning how to regulate the school life team for CPE, specifying the anchoring in a sociocognitive approach to learning, and explaining the research methodology, the article presents the main results. It seems that CPES share the conception of management based on an ethics of care, aligned with a participatory and formative aim. This orientation of professional practices can generate tensions.